PERIODE KRITIS TANAMAN MENTIMUN (Cucumis sativus L.) TERHADAP PERSAINGAN GULMA PADA TANAH SPODOSOL: PCRITICAL PERIOD OF CUCUMBER (Cucumis Sativus L.) PLANT AGAINST WEED COMPETTITION IN SPODOSOL SOIL - Abdul Hamid, Syahrudin; Tinting Sirenden, Ruben; Galih Prasetyo, Fitra; Zubaidah, Siti; Amelia, Vera; Vetrani Asie , Kambang; Syahid, Abdul (Fakultas Pertanian Universitas Palangka Raya, 2025)
This study aims to determine the critical period for cucumber (Cucumis sativus L.) plant against weed compettition in spodosol soil.The research was carried out on Jalan Merdeka, Jekan Raya District, Palangka Raya City, Central Kalimantan Province. The research was carried out in April-July 2024. This study used a Randomized Block Design (RAK) with treatment G1: Weed Free 10 DAP, G2: Weed Free 20 DAP, G3: Weed Free 30 DAF, G4: Weed Free Forever, G5: Weed 10 DAP, G6: Weed 20 DAP, G7: Weed 30 DAP and G8: Weed Forever. The results showed that weeding time for cucumber plants had a significant effect on plant length, number of leaves, number of productive branches, fruit diameter, fruit length and number of fruit per plot. The most dominant weed found on the research land is chicken claw grass (Digitaria ciliaris) both early and late vegetation analysis. The critical period for cucumber plants (Cucumis sativus L.) due to competition with weeds in spodosol soil is 0-20 days after plant Keywords: Critical period, Cucumber plants, Weeds, Spodosol